Bubble-based acoustic micropropulsors: active surfaces and mixers. Issue 8 (4th April 2017) - Bertin, Nicolas; Spelman, Tamsin A.; Combriat, Thomas; Hue, Hervé; Stéphan, Olivier; Lauga, Eric; Marmottant, Philippe
Abstract : Bubble-based acoustic propulsors are fabricated with 3D micro-printing. They generate collective flows used for fast and efficient mixing in microchannels. Abstract : Acoustic micropropulsors present great potential for microfluidic applications. The propulsion is based on encapsulated 20 μm bubbles excited by a contacless ultrasonic transducer. The vibrating bubbles then generate a powerful streaming flow, with speeds 1–100 mm s −1 in water, through the action of viscous stresses. In this paper we introduce a full toolbox of micropropulsors using a versatile three-dimensional (3D) microfabrication setup. Doublets and triplets of propulsors are introduced, and the flows they generate are predicted by a theoretical hydrodynamic model. We then introduce whole surfaces covered with propulsors, which we term active surfaces. These surfaces are excited by a single ultrasonic wave, can generate collective flows and may be harnessed for mixing purposes. Several patterns of propulsors are tested, and the flows produced by the two most efficient mixers are predicted by a simple theoretical model based on flow singularities. In particular, the vortices generated by the most efficient pattern, an L-shaped mixer, are analysed in detail.